Analysis and simulation of carriers statistic for semiconducting single wall carbon nanotube - Ismail, Razali (Matrice Technology Ltd., 2009)
In scaling down to 10 nm, the electron transportation is predominantly ballistic. Moreover, in most of the doped nanoscale devices, the carrier density is in the degenerate regime. In these cases the failure of Boltzmann statistic has led the research to new explanations. In this paper the authors formulate and simulate the carrier concentration in a semiconducting single wall carbon nanotube using the Fermi-Dirac distribution function. It was shown that the band structure of semiconducting single wall carbon nanotube nearby the minimum energy is parabolic and density of state is proportional to the Fermi-Dirac distribution. In the non-degenerate regime, Fermi energy is a weak logarithmic function of carrier concentration and varies linearly with temperature, but for strongly degenerate statistics, the Fermi energy is a strong function of carrier concentration and is independent of temperature.